Analysis of synchronous machines - Lipo, T. A. (Taylor & Francis, 2012)
"PREFACE The material in this book has evolved from a course taught yearly to senior/ graduate students entitled "Theory and Control of Synchronous Machines" at the University of Wisconsin. Begun in 1980, the essence of the course material has not changed substantially. However the means by which the course is taught has changed dramatically with the evolution of computing tools. The ready availability of MATLABTM and MATHCADTM has rendered many of the traditional methods of problem solving such as analog simulation, FORTRAN programming, constructional phasor diagrams and so forth, to be mere anecdotes. As a result of these powerful tools, over the years, material has been increasingly added so as to challenge the student and provide a deeper appreciation of the underlying theory of the subject. In particular, the material contained in Chapters 8-11 are rarely included in an introductory course and, if desired, could easily be omitted from a 3 credit course on this subject. These chapters are typically presented by the author as the background material for a lengthy "class problem" near the end of the semester which serves to cap the student's learning experience. I might add, with some delight, that these computational tools have even added to the "fun" of learning a challenging new subject. Thomas A. Lipo Madison WI February 2008"--